Establishing a Provincial Registry for Recurrent Prostate Cancer: Providing Access to PSMA PET/CT in Ontario, Canada - Young, Sympascho; Metser, Ur; Sistani, Golmehr; Langer, Deanna L.; Bauman, Glenn (Frontiers in Oncology, 2021)
Prostate Specific Membrane Antigen (PSMA) positron emission tomography/ computed tomography (PET/CT) is becoming established as a standard of care for the (re)staging of high-risk primary and prostate cancer recurrence after primary therapy. Despite the favorable performance of this imaging modality with high accuracy in disease detection, the availability of PSMA PET/CT varies across jurisdictions worldwide due to variability in the selection of PSMA PET/CT agent, regulatory approvals and funding. In Canada, PSMA based radiopharmaceuticals are still considered INDs, creating limitations in the deployment of these promising imaging agents. While regulatory approval rests with Health Canada, as a single payer health system, funding for Health Canada approved drugs and devices is decided by Provincial Health Ministries. Ontario Health (Cancer Care Ontario) (OH-CCO) is the agency of the Ministry of Health (MOH) in Ontario responsible for making recommendations to the MOH around the organization and funding of cancer services within Ontario (population of 15 million), and the PET Steering Committee of OH-CCO is responsible for providing recommendations on the introduction of new PET radiopharmaceuticals and indications. For Health Canada approved PET radiopharmaceuticals like 18F-FDG, OH-CCO (on behalf of the MOH) provides coverage based on levels of evidence and specific PET Registries are established to aid in real-world evidence collection to inform OH-CCO regarding emerging PET applications. In the case of PSMA PET/CT, adapting this model to an IND PSMA PET/CT agent, 18F-DCFPyL, necessitated the creation of a hybrid Registry-Study model to leverage the existing OH-CCO Registry structure while respecting the need for a Health Canada Clinical Trials Application (CTA) for the deployment of this agent in the province. Within the first 2 years of the registry, over 1700 men have been imaged resulting in a change in management (compared to pre-PET management plans) in over half of the men imaged. In this article, we describe the organization and deployment of the PSMA PET/CT (PREP) Registry throughout the province to provide access for men with suspected prostate cancer recurrence along with key stakeholder perspectives and preliminary results.